Solidification Behavior of Undercooled Fe75B25 Alloy - Changsong Ma; Lin Yang; Jinfu Li (Metals, 2023)
The paper presents a study of the phase selection and microstructure evolution of Fe75B25 alloy subjected to solidification at various undercoolings. The alloy invariably solidifies into a primary Fe2B phase and α-Fe/Fe2B eutectic at all the experimental undercoolings up to 381 K. A metastable Fe3B phase does not precipitate, although its growth in this alloy is favored without large-scale solute diffusion involved. It is shown that the phase selection is nucleation-controlled. Solid sites existing in the alloy melt seem more favorable for the nucleation of the Fe2B phase. As undercooling increases, primary the Fe2B phase changes its morphology complexly. It solidifies into coarse faceted dendrites at low undercoolings, developed non-faceted dendrites at moderate undercoolings, seaweeds with dense branches at higher undercoolings, and refined granular grains at undercooling above 147 K.